Modeling and optimization of thermal energy storage system in Engineering Complex, UiTM Shah Alam / Abdul Hafiz Kassim - Kassim, Abdul Hafiz (2014)
Thermal Energy Storage (TES) system has being established for quite some time and already being used in many places throughout the world. In Malaysia, several places had applied this system as an air-conditioning system in the building. Generally, TES is good for a country because it will normally reduce the overall maximum demand by distributing the load but the electricity tariff should be attractive so that the user will get the benefit. In order to make the C2 tariff more attractive, the off-peak energy (kWh) rate must be low enough and maximum demand (kW) rate should be the same with the Cl maximum demand tariff. The purpose of modeling is to be able to simulate the phenomenon between electrical energy (kWh) as the input and refrigerant ton hour (RTh) as the output. With the model, it enables the phenomenon to be predicted. The purpose of optimization is to minimize the input with certain design output or to maximize RTh output with certain energy (kWh) input. The methodology of this study is by calculating the overall cost, using Cl tariff as a benchmark to compare with the C2 tariff. The TES system in Engineering Complex UiTM is being used as the case study. The total costs that involved could be calculated. From this study, it was found that TES system uses more energy and electricity tariff play a very important role to determine its feasibility. The maximum cooling load required is 35,000 RTh with the maximum cooling load demand is 3,500 RT. Considering the optimal usage of 80%, the maximum designed need is 2,880 RT. The study shows that the present tariff set by power utility leads to a conclusion that if the cooling load storage is less than 60% of the total cooling need of a building, it is not feasible to operate TES system. Original TES design was 10,800 RTh, which is 30% which is then not feasible.